Mobile class attendance application system (MobCAS) / Muhammad Ridhwan Muhamidon - Muhamidon, Muhammad Ridhwan (2015)
Current class attendance system in UiTM is still using the manual form to collect attendance with is collect signature of the student. Many neglected occurs when using the manual collection attendance system, including missing of attendance paper when needed and trouble to lecturer to calculate the percentage of absenteeism. The main purpose of the project is to develop a mobile application for class attendance record called MobCAS and provide the percentage of student absenteeism. This project development in android application because android is widely used and easy to create. This project uses phpMy Admin as database and communicate using a web server. The purpose of using phpMy Admin as a database for MobCAS used by many users at one time. The results measured of learnability, effectiveness and acceptance of the application. For learnability, 30 percent respondent strongly agrees, 60 percent agree and only 10 percent disagree about the leamability of the application. For effectiveness, 30 percent strongly agree, 50 percent only agree and 20 percent of respondents not agree about the effectiveness of the application. Over 60 percent of respondents accept and interested to use MobCAS and the remaining are not interested.